Pengaruh pemberian konseling terhadap perubahan indeks massa tubuh anak usia 10-12 tahun - Rahmy, Hafifatul Auliya; Prativa, Nurul (Jurnal Cakrawala Promkes, 2021)
Obesity in childhood can increase the incidence of type 2 diabetes mellitus (DM). It is also at risk of becoming obese in adulthood. May cause glucose metabolism disorders and degenerative diseases. Besides, obesity in children aged 6-7 years can also reduce intelligence level due to decreased activity and creativity of children, and tend to be lazy due to being overweight. This type of research is a quasi-experimental one-group pre-post test design. The population in this study were all elementary school students in the work area of Puskesmas Andalas. Body Mass Index (BMI) was collected by measuring height and weight using a digital scale and microtoice. Nutrition counselling using leaflet media. Energy intake data collection before and after counselling used the Food Frequency Questionnaire and the 24-hour recall. The researcher collected characteristics data, physical activity data, body weight data, Body Mass Index data using a questionnaire and analysis of differences in BMI before and after the intervention using the dependent sample t-test. The results have a distinction between BMI before and after the intervention. Treatment of obesity in childhood with nutritional balance includes eating a variety of foods, doing physical activity, and regularly monitoring body weight.